Improving food security through quantification of food waste: a small study at University's cafeterias - Md Daud, Rafidah; Abdul Rahman, Haliza; Naim, Faridah (Human Resource Management Academic Research Society, 2022)
Food loss and waste are mainly occur in developing and industrialised Asian countries due to spoilage in warm and humid climates. Service is one of the main food waste generator including restaurants and institutions. This study aimed to investigate and quantify the food waste generated from cafeterias in Universiti Sains Malaysia Health Campus (USMKK). Weighing of food waste were conducted daily and repeated for three cafeterias within five weeks using portable hanging weight scales. Questionnaire were distributed randomly to 369 respondents. This survey was conducted to investigate customers’ opinions on food waste issues within university cafeterias. The number of customers was determined using a checklist. The results indicated that USMKK cafeterias generated average of 71.78 kg avoidable food waste and 275.93 kg unavoidable food waste. 26% of the customers claimed that they were regularly leave a quarter plate or bowl of uneaten food. Significant positive correlations (p<0.001) were found between number of customers and amount of food waste generated at the cafeterias. Factors that influence the generation of food waste at the cafeterias were include poor food quality, lack of freshness of the food, habits of consuming little amount of food and hours of operation of the cafeterias. The amount of avoidable and unavoidable food waste generated between the three cafeterias were significantly difference (p=0.001). Awareness campaign could increase the level of knowledge about food waste among customers. This would help the top management to plan suitable programme in minimising the production of food waste as to support sustainable environment.